The Excavation of Coull Castle, Aberdeenshire (Proceedings of the Society of Antiquaries of Scotland, 1924)
The castle, which was the seat of the Durwards is located next to the medieval church. A historical background with documentary records is presented. Erected comparatively early in the thirteenth century, the Castle of Coull belongs to the older type of stone fortress characterised by a single envelope and the presence of a donjon. The excavation is described in detail with many plans and illustrations. All of the surviving components of the castle have been revealed. The ruins are now in very poor condition. A detailed report on the pottery and other artefacts is included.